Analysis of production routes for silicon carbide using air as carbon source empowering negative emissions - Andreas Mühlbauer; Dominik Keiner; Tansu Galimova; Christian Breyer (Mitigation and Adaptation Strategies for Global Change, 2024)
AbstractA rapid defossilisation of the industry sector is required to stop further greenhouse gas emissions and to curb global warming. Additionally, to avoid irreversible consequences caused by climate change, the deployment of negative emission technologies is required to reduce the carbon dioxide (CO2) concentration in Earth's atmosphere to a sustainable level. A novel approach to store gaseous CO2 from direct air capture facilities in solid silicon carbide (SiC) is presented. A chain of established processes to produce SiC from renewable electricity and air is evaluated in terms of energy and mass balances. Furthermore, possible fields of SiC utilisation are considered. Electricity-based SiC (e-SiC) can serve the growing global market for technical ceramics and can possibly be used to tackle increasing construction sand shortages in the construction industry by partially substituting sand. Calculations of the levelised cost of carbon dioxide removal show that storing ambient CO2 in solid SiC that can be subsequently sold on the world market can eventually create profit. In 2050, a net benefit of 259 exteuro/tCO2 or 631 exteuro/tSiC can be realised if the SiC product is sold at the world market with additional carbon compensation. Therefore, the proposed SiC production chain might be able to challenge conventionally produced SiC, while empowering negative emissions. In 2050, the net CO2 emission potential is limited to about 290 MtCO2/a for technical ceramics, but may reach up to 13.6 GtCO2/a for construction sand. Results show that e-SiC production is economically feasible for technical ceramics but not for construction sand without further process cost decrease. Alternative processes to produce e-SiC are described and evaluated. Future research opportunities are discussed.
Keywords: 330; Negative emissions; Silicon carbide; Carbon dioxide removal; Defossilisation; Industry; Power-to-X